The Relationship between the Profiles of SVC and Sustainability of SVC Fibrillation Induced by Provocative Electrical Stimulation. Issue 4 (18th February 2016) - NAKAMURA, TOMOFUMI; HACHIYA, HITOSHI; YAGISHITA, ATSUHIKO; TANAKA, YASUAKI; HIGUCHI, KOJI; KAWABATA, MIHOKO; SASANO, TETSUO; HIRAO, KENZO
Abstract : Background: Superior vena cava (SVC) can be a focus of atrial fibrillation (AF). However, distinctive features that identify SVC arrhythmogenicity remain unclear. Sustainability of fibrillation within the SVC might help with identifying SVC arrhythmogenicity. The purpose of this study was to investigate the relationship between the anatomical and electrical profiles of SVC and sustainability of SVC fibrillation induced by proactive electrical stimulation. Methods: Consecutive 36 patients with paroxysmal or persistent AF who underwent repetitive pulmonary vein isolation (PVI) session were included in the study. After successful PVI, periodic rapid electrical stimuli were delivered to the SVC to induce SVC fibrillation. SVC fibrillation was defined as follows: (1) the local fibrillatory electrical activity persisted longer than 3 seconds, (2) the local fibrillatory activity penetrated through the atrium and maintained AF, and (3) the frequency of local activity was higher than that of any other atrial components such as coronary sinus and right atrial appendage. Results: SVC fibrillation was induced in seven patients. The group with SVC fibrillation had significantly longer SVC sleeve and longer left atrial diameter compared with the group without SVC fibrillation. All patients with SVC fibrillation were free from AF recurrence after SVC isolation. Conclusions: The SVC sleeve longer than 30 mm had sustainability of SVC fibrillation induced by electrical stimulation. This finding advocates that arrhythmogenic substrate may exist in the SVC with long myocardial sleeve.